Assembly of 1D Cadmium(II) Coordination Polymer with Bis(2-benzimidazole) and 1,3-Benzenedicarboxylic Acid Mixed Ligands - Feng, Guo-Dong; Jiang Xiao-Lin Luo, Luan; Wang, Min-Juan (Asian Journal of Chemistry, 2013)
A novel one-dimensional cadmium(II) compound: [CdL(H2C2EIm)(H2O)](H2O)2n (1) with 1,3-benzene dicarboxylic acid (H2L) and 2,2'-(1,2-ethanediyl)bis(1H-benzimidazole) (H2C2EIm) has been synthesized by means of hydrothermal method and characterized by X-ray single-crystal diffraction. The crystal belongs to the triclinic system triclinic, space group P-1 with a = 1.0189(5) nm, b = 1.1204(5) nm, c = 1.2319(5) nm, a = 115.824(5)º, b = 98.363(5)º, g = 102.654(5)º, V = 1.1878(9) nm3, Dc = 1.649 g cm-3, Z = 2, F(000) = 594, Goof= 0.997, R1 = 0.0358, wR2 = 0.0881. The compound 1 shows a novel one-dimensional (1D) chain structure along the c axis and further extended into a 1D double chain structure through p-p packing interactions. The intermolecular hydrogen bonds contribute to the formation of the three-dimensional supramolecular architecture and stabilize the crystal structure.